Digital Marketing Integration Strategy to Support Online Campaigns in Pearung Tourism Village, Humbang Hasundutan Regency, North Sumatra - Tambunan, Ellyta; Bastanta Eka Putra Kembaren; Riana Handayani Silalahi (Formosa Journal of Multidisciplinary Research, 2024)
Analysis of the Influence of Digital Marketing Strategies and Online Campaigns on Tourist Visit Rates in Pearung Geosite Sipinsur Village, Humbang Hasundutan Regency, North Sumatra. This study aims to analyze the influence of digital marketing strategies and online campaigns on tourist visit rates in Pearung Geosite Sipinsur Village, Humbang Hasundutan Regency, North Sumatra. Research Method : This study uses a quantitative method with a survey technique. Data was collected through questionnaires distributed to 100 respondents who had visited Pearung Geosite Sipinsur Village. The data was analyzed using simple linear regression. Research Results: The results showed that Digital marketing strategies implemented by Pearung Geosite Sipinsur Village are less good. Online campaigns carried out are considered good enough. There is a strong relationship between digital marketing strategies and online campaigns on tourist visit rates. Digital marketing strategies have an influence of 80.4% on tourist visit rates in Pearung Geosite Sipinsur Village. Conclusion : The implementation of effective digital marketing strategies and good online campaigns can increase tourist visit rates in Pearung Geosite Sipinsur Village.